Positive electrode active material, positive electrode plate, secondary battery and electric device
By using a combined material composed of secondary particles and single crystal or single crystal-like particles in the positive electrode active material of secondary batteries, the problem of difficulty in taking into account the cost and performance of secondary batteries is solved, and a balance between low cost and high cycle stability is achieved.
Patent Information
- Application Number
- CN202311070156.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-23
AI Technical Summary
It is difficult for existing secondary batteries to take into account high electrochemical properties while reducing costs, especially in the selection of positive electrode active materials, which are often difficult to take into account both cost and performance.
Using a positive electrode active material composed of secondary particles and single crystal or single crystal-like particles, the secondary particles are formed by aggregation of primary particles and contain M1 elements (such as Ni, Cr, Cu, Zn, Co, Mn), while single crystal or single crystal-like particles contain Ma elements (such as Ni, Cr, Cu, Zn, Co, Mn). By adjusting the content and particle size of these elements, the dynamic performance and cycling stability of the battery are improved.
The secondary battery is balanced between low cost and high cycle stability, reducing the battery's self-discharge phenomenon, and improving the compaction density and cycle performance of the battery.
Smart Images

Figure CN119517946A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode active material, a positive electrode sheet, a secondary battery and an electrical device. Background Art
[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's requirements for the cost and performance of secondary batteries have become increasingly stringent.
[0003] In the prior art, it is often difficult to balance the cost and performance of secondary batteries. How to reduce the cost of secondary batteries while taking into account their electrochemical performance has become an urgent problem to be solved. Summary of the invention
[0004] In view of the problems existing in the background technology, the present application provides a positive electrode active material, a positive electrode plate, a secondary battery and an electric device, so that the secondary battery has both low cost and high performance.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The first aspect of the present application provides a positive electrode active material, which includes (i) secondary particles and (ii) single crystals or quasi-single crystal particles, wherein the secondary particles are mainly formed by aggregation of primary particles and the secondary particles further contain an M1 element, wherein the M1 element contains transition metal elements other than iron, and the mass content of the M1 element based on the total mass of the secondary particles is X1, 500ppm≤X1≤5000ppm, optionally 800ppm≤X1≤2000ppm; the single crystals or quasi-single crystal particles contain an Ma element, wherein the Ma element contains transition metal elements other than iron, and the mass content of the Ma element based on the total mass of the single crystals or quasi-single crystal particles is X2, and X2 is less than X1.
[0007] In order to prepare low-cost positive electrode active materials, low-cost raw materials are needed. Using byproducts recycled from steel mills or products recovered from positive electrode materials as iron sources to prepare positive electrode active materials, such as lithium iron phosphate, can significantly reduce the cost of positive electrode active materials. However, byproducts recycled from steel mills often contain other transition metal impurities, such as nickel, cobalt, chromium, etc. The lithium deduction cost of secondary particles containing M1 elements with a mass content of 500ppm-5000ppm is only 60%-70% of the cost of commercial positive electrode active materials in the prior art.
[0008] The presence of impurities in the positive electrode active material will reduce the capacity of the positive electrode active material. Forming low-cost positive electrode active materials into secondary particles formed by the aggregation of small-sized primary particles is conducive to improving the kinetic performance of secondary batteries, thereby improving the capacity level of secondary batteries to compensate for the decrease in secondary battery capacity caused by impurities. However, there are many grain boundaries in the secondary particles, and transition metal impurities are easily dissolved during the cycle, migrate to the negative electrode and are reduced at the negative electrode, aggravating the self-discharge phenomenon of the battery. Single crystals or quasi-single crystal particles with relatively low impurity content have higher structural stability and cycle stability, can reduce the dissolution of transition metal impurities, and their cooperation with secondary particles will increase the migration path length and tortuosity of transition metal impurities, reduce the amount of transition metal deposition at the negative electrode, improve the uniformity of transition metal deposition at the negative electrode, reduce the probability of transition metal ions directly depositing at the negative electrode to produce dendrites, and alleviate the self-discharge phenomenon of the battery.
[0009] In any embodiment, the single crystal or quasi-single crystal particles contain Ma elements, and the Ma elements contain transition metal elements other than iron. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content X2 of the Ma element is 20ppm-450ppm, and can be optionally 100ppm-300ppm.
[0010] The single crystal or quasi-single crystal particles within the above mass content range can further inhibit the precipitation of transition metal elements from the positive electrode, reduce the self-discharge phenomenon of the battery, and improve the cycle stability of the battery. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content X2 of the Ma element is 100ppm-300ppm, which can further take into account the low cost and good cycle stability of the battery.
[0011] In any embodiment, the secondary particles further contain M2 elements, and the M2 elements contain at least one of alkali metal elements, alkaline earth metal elements, and boron group elements except lithium elements. Based on the total mass of the secondary particles, the mass content of the M2 element is 50ppm-8000ppm, and can be optionally 1000ppm-5000ppm.
[0012] The cost of positive electrode active materials can be further reduced by using industrial-grade lithium carbonate, quasi-battery-grade lithium carbonate extracted from salt lakes, and agricultural-grade phosphoric acid as lithium and phosphorus sources to prepare positive electrode active materials, such as lithium-containing phosphates. However, industrial-grade lithium carbonate and agricultural-grade phosphoric acid often contain high levels of alkali metal elements, alkaline earth metal elements, and boron elements other than lithium. The cost of secondary particles with a mass content of M2 elements between 650ppm and 8000ppm is further reduced, which further reduces the cost of batteries.
[0013] The presence of high content of alkali metal elements, alkaline earth metal elements, and boron group elements impurity elements other than lithium in the positive electrode active material will block the transmission channel of active ions, further deteriorate the kinetic performance and gram capacity of the positive electrode active material, and reduce the gram capacity performance of the secondary battery. Based on the total mass of the secondary particles, the positive electrode active material with a mass content of 1000ppm-5000ppm of M2 elements can further take into account the cost and high gram capacity level of the secondary battery.
[0014] In any embodiment, the single crystal or quasi-single crystal particle further contains Mb element, and the Mb element contains at least one of alkali metal elements, alkaline earth metal elements, and boron group elements except lithium element. Based on the total mass of the single crystal or quasi-single crystal particle, the mass content of the Mb element is 20ppm-550ppm, and can be optionally 100ppm-300ppm.
[0015] The single crystal or quasi-single crystal particles within the above mass content range can improve the capacity level of the battery. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content of the Mb element is 100ppm-300ppm, which can further take into account the low cost and high gram capacity level of the battery.
[0016] In any embodiment, the average particle size of the secondary particles is r, the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤r / R2≤30, and can be optionally 4≤r / R2≤10.
[0017] By matching the size of secondary particles with single crystal or quasi-single crystal particles, the compaction density of the pole piece can be increased, the cracking of the positive electrode active material during rolling and use can be reduced, and the cycle performance of the secondary battery can be improved. The positive electrode active material with 4≤r / R2≤10 can further improve the compaction density and cycle performance of the battery.
[0018] In any embodiment, the average particle size of the primary particles is R1, the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤R2 / R1≤20, and can be optionally 6≤R2 / R1≤10.
[0019] The cathode active material achieves a balance between kinetic performance and cycle stability by matching the size of the primary particles of the secondary particles with the single crystal primary particles. The cathode active material with 6≤R2 / R1≤10 can further take into account the kinetic performance and cycle stability of the battery.
[0020] In any embodiment, the average particle size r of the secondary particles is 1.2um-18um, and can be optionally 2.4um-6um.
[0021] The average particle size of the secondary particles within this range can effectively improve the compaction density of the pole piece and reduce the rupture of the positive electrode active material during rolling and use. Due to the large average particle size of the secondary particles, the dissolution rate of the M1 element can be slowed down, and the cycle performance of the secondary battery can be improved. The average particle size r of the secondary particles is 2.4um-6um, which can further improve the compaction density and cycle performance of the battery, and at the same time, it can produce a more effective combination with single crystal or quasi-single crystal particles.
[0022] In any embodiment, the average particle size R1 of the primary particles is 30 nm-300 nm, and can be 60 nm-100 nm.
[0023] The average particle size of the primary particles within this range helps to increase the compaction density of low-cost pole pieces and improve the gram capacity of secondary batteries. The average particle size R1 of the primary particles is 60nm-100nm, which can reduce the impact of impurities in the secondary particles on the gram capacity while reducing the impact of impurities and single crystal or quasi-single crystal particles on the kinetic performance of secondary batteries, thereby improving the kinetic performance of secondary batteries. The primary particles are designed to be nanometer-level, which can reduce the impact of impurities in the positive electrode active material on the battery rate, low temperature performance and capacity.
[0024] In any embodiment, the mass ratio of the secondary particles to the single crystal or quasi-single crystal particles is 1:9-4:6, and can be optionally 2:8-3:7.
[0025] The blending of single crystal or quasi-single crystal particles and secondary particles can dilute the ion dissolution effect of the secondary particles and balance the gram capacity and cycle stability of the secondary battery.
[0026] The positive electrode active material within the above range can achieve both low cost and good electrochemical performance of the secondary battery.
[0027] In any embodiment, M2 and Mb each independently include at least one of Na, K, Ca, Al, and Mg, and M1 and Ma each independently include at least one of Ni, Cu, Zn, Mn, Cr, and Co.
[0028] In any embodiment, the positive electrode active material includes lithium-containing phosphate. Optionally, the positive electrode active material includes lithium iron phosphate and a coating modification material thereof.
[0029] A second aspect of the present application provides a positive electrode plate, comprising a positive electrode film layer, wherein the positive electrode film layer comprises a positive electrode active material according to any embodiment.
[0030] The positive electrode sheet has low cost and high compaction density.
[0031] A third aspect of the present application provides a secondary battery, comprising the positive electrode active material of any embodiment or the positive electrode plate of any embodiment.
[0032] The secondary battery has low cost and high cycle stability.
[0033] In any embodiment, the secondary battery further includes a separator, and the separator includes at least one of hydroxyl, amino, carboxyl, and ester functional groups.
[0034] The isolation membrane can chelate or adsorb the transition metal ions dissolved in the positive electrode active material to form a stable metal chelate or adsorbate through the functional groups on its surface when the transition metal ions diffuse from the positive electrode to the negative electrode, effectively preventing the transition metal ions from migrating to the negative electrode, effectively reducing the damage of the transition metal ions to the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode, and also effectively reducing the reduction of the transition metal ions to metal elements at the negative electrode, which is beneficial to improving the capacity retention rate of the secondary battery.
[0035] A fourth aspect of the present application includes an electrical device including the secondary battery of any embodiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a scanning electron microscope image of a cross section of a positive electrode sheet according to an embodiment of the present application;
[0037] Figure 2 is a scanning electron microscope image of a cross section of a secondary particle according to an embodiment of the present application;
[0038] Figure 3 is a scanning electron microscope image of a cross section of a single crystal or quasi-single crystal particle according to an embodiment of the present application;
[0039] Figure 4 It is a schematic diagram of the structure of the positive electrode sheet according to one embodiment of the present application;
[0040] Figure 5 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0041] Figure 6 yes Figure 5 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0042] Figure 7 It is a schematic diagram of an electrical device according to one embodiment of the present application.
[0043] Reference numerals:
[0044] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 positive electrode sheet; 61 positive electrode film layer; 62 secondary particles; 63 single crystal or quasi-single crystal particles; 64 primary particles; 65 positive electrode current collector. DETAILED DESCRIPTION
[0045] Hereinafter, the embodiments of the positive electrode active material, secondary battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0050] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0051] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0052] Lithium secondary batteries are widely used in front-end technology fields such as digital and electric vehicles due to their high energy density, high voltage and long service life. Lithium iron phosphate material is a commonly used positive electrode active material for lithium secondary batteries. When lithium iron phosphate granular materials with high purity and few impurities are used in secondary batteries, the high cost of the battery makes it difficult to reduce the selling price of electrical devices. The use of low-cost raw materials such as industrial-grade lithium carbonate, agricultural-grade phosphoric acid, secondary recycled iron phosphate, and by-products recycled from steel mills to prepare positive electrode active materials can significantly reduce the raw material cost of secondary batteries, but at the same time, the electrochemical performance of the secondary batteries prepared by them is low and it is difficult to meet the use requirements.
[0053] [Positive electrode active material]
[0054] Based on this, the present application provides a positive electrode active material, which includes (i) secondary particles and (ii) single crystals or quasi-single crystal particles, the secondary particles are mainly formed by aggregation of primary particles and the secondary particles also contain M1 elements, the M1 elements contain transition metal elements other than iron, and based on the total mass of the secondary particles, the mass content of the M1 element is X1, 500ppm≤X1≤5000ppm, optionally 800ppm≤X1≤2000ppm; the single crystals or quasi-single crystal particles contain Ma elements, the Ma elements contain transition metal elements other than iron, and based on the total mass of the single crystals or quasi-single crystal particles, the mass content of the Ma element is X2, and X2 is less than X1.
[0055] In this context, secondary particles refer to agglomerates formed by the aggregation of not less than five primary particles.
[0056] Herein, single crystal or quasi-single crystal particles refer to primary particles that are not aggregated or aggregates formed by aggregation of less than 5 primary particles.
[0057] In this document, ppm means parts per million.
[0058] In this context, transition metals are a series of elements in the d-block of the periodic table.
[0059] In some embodiments, the M1 element includes at least one of Ni, Cu, Zn, Mn, Cr, and Co.
[0060] In some embodiments, based on the total mass of the secondary particles, the mass content X1 of the M1 element is 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value therebetween.
[0061] In some embodiments, the difference between X1 and X2 is 50 ppm-4980 ppm.
[0062] In some embodiments, the difference between X1 and X2 can be 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 480ppm, 700ppm, 1450ppm, 1550ppm, 1700ppm,
[0063] 1900ppm, 1980ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500m,
[0064] 4900ppm, 4980ppm.
[0065] The morphology of the positive electrode active material can be tested by any method known in the art. As an example, the cross section of the positive electrode sheet can be observed by a scanning electron microscope to observe the morphology of the positive electrode active material. Figure 1 The cross-sectional morphology of the positive electrode sheet in any embodiment of the present application is shown. Figure 1 It can be seen that the positive electrode film layer 61 includes secondary particles 62 and single crystal or quasi-single crystal particles 63. The morphology of the secondary particles 62 is as follows: Figure 2 As shown in FIG. 1 , the secondary particles 62 have a larger particle size and are agglomerates formed by the aggregation of small-sized primary particles 64. The morphology of the single crystal or quasi-single crystal particles 63 is as follows: Figure 3 As shown, the primary particles 64 are larger than the secondary particles, but smaller than the secondary particles 62. The sizes of the secondary particles 62 and the single crystal or quasi-single crystal particles 63 are obtained by statistics, and the secondary particles 62 and the single crystal or quasi-single crystal particles 63 are screened according to the difference in their particle sizes, or the secondary particles 62 and the single crystal or quasi-single crystal particles 63 are separated according to the different sedimentation speeds of the two in the mixed solution of alcohol and water, and then the mass content of the particle elements is tested and analyzed by inductively coupled plasma.
[0066] In order to prepare low-cost positive electrode active materials, low-cost raw materials need to be used. The cost of positive electrode active materials, such as lithium iron phosphate, can be significantly reduced by using byproducts recycled from steel mills or recycled materials from batteries. However, byproducts recycled from steel mills or recycled materials from batteries often contain other transition metal impurities, such as nickel, cobalt, chromium, etc. The cost of secondary particles containing M1 elements with a mass content of 500ppm-5000ppm is only 60%-70% of the cost of commercial positive electrode active materials in the prior art.
[0067] The presence of impurities in the positive electrode active material will reduce the capacity of the positive electrode active material. Forming the low-cost positive electrode active material into secondary particles formed by the aggregation of small-sized primary particles is conducive to improving the kinetic performance of the secondary battery, thereby improving the capacity level of the secondary battery to compensate for the decrease in the capacity of the secondary battery caused by impurities. However, there are many grain boundaries in the secondary particles, and transition metal impurities are easily dissolved during the cycle, migrate to the negative electrode and are reduced at the negative electrode, aggravating the self-discharge of the battery and causing a significant attenuation of the battery cycle capacity retention rate. Single crystal or quasi-single crystal particles with relatively low impurity content have higher structural stability and cycle stability, can reduce the dissolution of transition metal impurities, and their cooperation with secondary particles will increase the migration path length and tortuosity of transition metal impurities, reduce the deposition of transition metals at the negative electrode, improve the uniformity of transition metal deposition at the negative electrode, and alleviate the self-discharge of the battery.
[0068] The positive electrode active material having a mass content X1 of the M1 element of 400 ppm to 2000 ppm based on the total mass of the secondary particles can further take into account both low cost and good cycle stability of the battery.
[0069] In some embodiments, the single crystal or quasi-single crystal particles contain Ma elements, and the Ma elements contain transition metal elements other than iron. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content X2 of the Ma element is 20ppm-450ppm, and can be optionally 100ppm-300ppm.
[0070] In some embodiments, the single crystal or quasi-single crystal particle contains Ma element, and the Ma element contains a transition metal element other than iron. Based on the total mass of the single crystal or quasi-single crystal particle, the mass content X2 of the Ma element can be selected to be 20ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm or any value therebetween.
[0071] The single crystal or quasi-single crystal particles within the above mass content range can further inhibit the precipitation of transition metal elements from the positive electrode, reduce the self-discharge phenomenon of the battery, and improve the cycle stability of the battery. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content X2 of the Ma element is 100ppm-300ppm, which can further take into account the low cost and good cycle stability of the battery.
[0072] In some embodiments, the secondary particles further contain M2 elements, and the M2 elements contain at least one of alkali metal elements, alkaline earth metal elements, and boron group elements except lithium elements. Based on the total mass of the secondary particles, the mass content of the M2 element is 650ppm-8000ppm, and can be optionally 1000ppm-5000ppm.
[0073] In this article, alkali metal elements refer to the six metal elements in Group IA of the periodic table except hydrogen (H), namely lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr).
[0074] In this article, alkaline earth metal elements refer to the IIA group elements in the periodic table, including beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra).
[0075] In this article, the boron group elements refer to the elements in Group ⅢA of the periodic table, including boron (B), aluminum (Al), gallium (Ga), indium (In), thallium (Tl), and niobium (Nh).
[0076] In some embodiments, the M2 element includes at least one of Na, K, Ca, Al, and Mg.
[0077] In some embodiments, based on the total mass of the secondary particles, the mass content of the M2 element is 650ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm or any value therebetween.
[0078] The cost of positive electrode active materials can be further reduced by using recycled positive electrode materials such as iron phosphate, industrial-grade lithium carbonate, quasi-battery-grade lithium carbonate extracted from salt lakes, and agricultural-grade phosphoric acid as lithium and phosphorus sources to prepare positive electrode active materials, such as lithium-containing phosphates. However, recycled products such as industrial-grade lithium carbonate and agricultural-grade phosphoric acid often contain high levels of alkali metal elements, alkaline earth metal elements, and boron group elements. The cost of secondary particles with a mass content of M2 elements of 1000ppm-8000ppm is further reduced, which further reduces the cost of batteries.
[0079] The presence of high content of alkali metal elements, alkaline earth metal elements, and boron group elements impurity elements other than lithium in the positive electrode active material will block the transmission channel of active ions, further deteriorate the kinetic performance and gram capacity of the positive electrode active material, and reduce the gram capacity performance of the secondary battery. Based on the total mass of the secondary particles, the positive electrode active material with a mass content of 1000ppm-5000ppm of M2 elements can further take into account the cost and high gram capacity level of the secondary battery.
[0080] In some embodiments, the single crystal or quasi-single crystal particle further contains Mb element, and the Mb element contains at least one of alkali metal elements, alkaline earth metal elements, and boron group elements except lithium element. Based on the total mass of the single crystal or quasi-single crystal particle, the mass content of the Mb element is 20ppm-500ppm, and can be optionally 100ppm-300ppm.
[0081] In some embodiments, based on the total mass of the single crystal or quasi-single crystal particle, the mass content of the Mb element may be 20 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm or any value therebetween.
[0082] The single crystal or quasi-single crystal particles within the above mass content range can improve the capacity level of the battery. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content of the Mb element is 100ppm-300ppm, which can further take into account the low cost and high gram capacity level of the battery.
[0083] In some embodiments, the average particle size of the secondary particles is r, the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤r / R2≤30, and can be optionally 4≤r / R2≤10.
[0084] The average particle size of the secondary particles and the average particle size of the single crystal or quasi-single crystal particles can be obtained by any known method in the art. As an example, the average particle size of the secondary particles and the average particle size of the single crystal or quasi-single crystal particles can be tested by scanning electron microscopy. The cross-section of the positive electrode plate is observed by scanning electron microscopy, and the Avizo 3D software is used to perform particle size area analysis on the obtained scanning electron microscope image of the cross section of the electrode plate, and the particle size of the positive electrode active material is calculated by fitting, and the total value of the statistical secondary particle size is divided by the total number of secondary particles as the average particle size r of the secondary particles; the total value of the statistical single crystal or quasi-single crystal particle size is divided by the total number of single crystal or quasi-single crystal particles as the average particle size R2 of the single crystal or quasi-single crystal particles.
[0085] In some embodiments, r / R2 can be selected as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30 or any value therebetween.
[0086] By matching the size of secondary particles with single crystal or quasi-single crystal particles, the compaction density of the pole piece can be increased, the cracking of the positive electrode active material during rolling and use can be reduced, and the cycle performance of the secondary battery can be improved. The positive electrode active material with 4≤r / R2≤10 can further improve the compaction density and cycle performance of the battery.
[0087] In some embodiments, the average particle size of the primary particles is R1, the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤R2 / R1≤20, and can be 6≤R2 / R1≤10.
[0088] The average particle size of the primary particles can be obtained by any known method in the art. As an example, a scanning electron microscope can be used to observe the cross-section of the secondary particles to observe their particle morphology, and the particle size of the primary particles inside the secondary particles can be measured, and the long diameter of the primary particles is used as the particle size of the primary particles, and the total value of the particle size of the primary particles divided by the total number of primary particles is used as the average particle size of the primary particles.
[0089] In some embodiments, the average particle size of the primary particles is R1, the average particle size of the single crystal or quasi-single crystal particles is R2, and R2 / R1 can be selected as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value therebetween.
[0090] The cathode active material achieves a balance between kinetic performance and cycle stability by matching the size of the primary particles of the secondary particles with the single crystal primary particles. The cathode active material with 6≤R2 / R1≤10 can further take into account the kinetic performance and cycle stability of the battery.
[0091] In some embodiments, the average particle size r of the secondary particles is 1.2um-18um, and can be optionally 2.4um-6um.
[0092] The average particle size r of the secondary particles can be selected as 1.2um, 2.4um, 3um, 4um, 5um, 6um, 7um, 8um, 9um, 10um, 11um, 12um, 13um, 14um, 15um, 16um, 17um, 18um or any value therebetween.
[0093] The average particle size of the secondary particles within this range can effectively increase the compaction density of the pole piece, reduce the rupture of the positive electrode active material during rolling and use, and improve the cycle performance of the secondary battery. The average particle size r of the secondary particles is 2.4um-6um, which can further improve the compaction density and cycle performance of the battery.
[0094] In some embodiments, the average particle size R1 of the primary particles is 30 nm-300 nm, and can be 60 nm-100 nm.
[0095] The average particle size R1 of the primary particles may be 30 nm, 50 nm, 60 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm or any value therebetween.
[0096] The average particle size of the primary particles within this range helps to increase the compaction density of low-cost pole pieces and improve the gram capacity of secondary batteries. The average particle size R1 of the primary particles is 60nm-100nm, which can reduce the impact of impurities in the secondary particles on the gram capacity while reducing the impact of impurities and single crystal or quasi-single crystal particles on the kinetic performance of secondary batteries, thereby improving the kinetic performance of secondary batteries.
[0097] In some embodiments, the mass ratio of the secondary particles to the single crystal or quasi-single crystal particles is 1:9-4:6, and can be optionally 2:8-3:7.
[0098] In some embodiments, the mass ratio of the secondary particles to the single crystal or quasi-single crystal particles may be 1:9, 4:6, 2:8, 3:7 or any value therebetween.
[0099] The positive electrode active material within the above range can achieve both low cost and good electrochemical performance of the secondary battery.
[0100] In some embodiments, M2 and Mb each independently include at least one of Na, K, Ca, Al, and Mg, and M1 and Ma each independently include at least one of Ni, Cu, Zn, Mn, Cr, and Co.
[0101] In some embodiments, the positive electrode active material includes lithium-containing phosphate. Optionally, the positive electrode active material includes lithium iron phosphate and a coating modification material thereof.
[0102] In some embodiments, the lithium iron phosphate includes Li 1+y1 Fe y2 P 1+y3 O 4+y4 , among which, 0≤y1≤0.2, 0.94≤y2≤1, 0≤y3≤0.1, -0.1≤y4≤0.1.
[0103] It should be noted that in the embodiments of the present application, the chemical formula of lithium iron phosphate is the chemical formula of the material used in the preparation process. In the positive electrode plates, battery cells, and electrical equipment, lithium ions will be consumed due to the processes of formation and circulation, so there will be a situation where the measured lithium content in the positive electrode active material decreases. At the same time, if the positive electrode plates and negative electrode plates are supplemented with lithium, after the processes of formation and circulation, there will be a situation where the measured lithium content in the positive electrode active material increases. In the positive electrode plates, battery cells, and electrical equipment, due to the processes of formation and circulation, it can be understood by those skilled in the art that the elements in the chemical formula of lithium iron phosphate may be lost. For example, phosphorus and oxygen will be consumed, so there will be a situation where the measured phosphorus content in the lithium iron phosphate decreases and / or the oxygen content decreases.
[0104] [Positive electrode]
[0105] A second aspect of the present application provides a positive electrode plate, comprising a positive electrode film layer, wherein the positive electrode film layer comprises the positive electrode active material according to any embodiment of the claims.
[0106] In some embodiments, the schematic diagram of the positive electrode structure is as follows Figure 4 As shown, the positive electrode sheet 6 includes a positive electrode current collector 65 and a positive electrode film layer 61 disposed on at least one surface of the positive electrode current collector 65 , wherein the positive electrode film layer 61 includes a positive electrode active material, and the positive electrode active material includes secondary particles 62 and single crystal or quasi-single crystal particles 63 .
[0107] The positive electrode sheet has low cost and high compaction density.
[0108] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0109] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0110] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0111] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0113] [Negative electrode]
[0114] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0115] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0116] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0117] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0118] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0119] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0120] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0121] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0122] [Electrolytes]
[0123] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0124] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0125] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0126] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0127] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0128] [Secondary battery]
[0129] A third aspect of the present application provides a secondary battery, comprising the positive electrode active material of any embodiment or the positive electrode plate of any embodiment.
[0130] The secondary battery has low cost and high cycle stability.
[0131] In some embodiments, the secondary battery further includes a separator, and the separator includes at least one of hydroxyl, amino, carboxyl, and ester functional groups.
[0132] The isolation membrane can chelate or adsorb the transition metal ions dissolved in the positive electrode active material to form a stable metal chelate or adsorbate through the functional groups on its surface when the transition metal ions diffuse from the positive electrode to the negative electrode, effectively preventing the transition metal ions from migrating to the negative electrode, effectively reducing the damage of the transition metal ions to the solid electrolyte membrane (SEI membrane) on the surface of the negative electrode, and also effectively reducing the reduction of the transition metal ions to metal elements at the negative electrode, which is beneficial to improving the capacity retention rate of the secondary battery.
[0133] In some embodiments, the isolation film includes a base layer and a functional coating located on at least one side of the base layer, wherein the functional coating includes an inorganic material, and the inorganic material optionally includes at least one of aluminum oxide, silicon dioxide, magnesium oxide, calcium oxide, and titanium oxide, and the surface of the inorganic material includes -OH, -NH 2 and at least one of -COOH.
[0134] In some embodiments, the material of the isolation membrane base layer can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0135] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0136] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0137] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0138] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0139] In some embodiments, reference Figure 6 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0140] [Electrical devices]
[0141] A fourth aspect of the present application provides an electrical device, comprising a secondary battery according to any embodiment.
[0142] The electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0143] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0144] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0145] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0146] Example
[0147] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0148] 1. Preparation method
[0149] Example 1
[0150] 1) Preparation of positive electrode active materials
[0151] Preparation method of secondary particles:
[0152] Dispersing and mixing a mixed carbon source of lithium carbonate, iron red, ammonium dihydrogen phosphate, glucose and polyethylene glycol (PEG) in water to obtain a mixture, wherein the molar ratio of Li:Fe:P in the mixed slurry is (1.01-1.03):(0.99-0.96):1; the solid content of the mixed slurry is 45%, the weight ratio of glucose to PEG is 2:1, and the molecular weight of PEG is 6000;
[0153] Iron red contains Ni, Cr, Cu, Zn, Co, and Mn impurities, and their total content is 3500ppm relative to the mass of iron red raw materials. Ammonium dihydrogen phosphate contains Na, K, Ca, Al, and Mg impurities, and their total content is 1000ppm relative to the mass of ammonium dihydrogen phosphate raw materials. The mixture is ground to obtain a mixture slurry; the mixture slurry is spray-dried and granulated to obtain a precursor; the precursor is pre-burned in oxygen to obtain a pre-burned product; the pre-burned product is sintered under a protective atmosphere of nitrogen, the sintering constant temperature is 740°C, and the constant temperature time is 8h to obtain a polycrystalline granular lithium iron phosphate material, and the material is demagnetized and sieved to obtain a lithium iron phosphate material with a secondary particle size of 6um.
[0154] Preparation method of single crystal or quasi-single crystal particles:
[0155] Lithium carbonate, iron red, ammonium dihydrogen phosphate, glucose and PEG mixed carbon source are dispersed and mixed in water to obtain a mixed slurry. After mixing, the molar ratio of Li:Fe:P in the slurry is (1.01-1.03):
[0156] (0.99-0.96): 1; the solid content of the mixed slurry is 45%; the iron ore contains Ni, Cr, Cu, Zn, Co, and Mn impurities, and their total content is 100ppm relative to the mass of the iron ore raw material; the diammonium phosphate contains Na, K, Ca, Al, and Mg impurities, and their total content is 100ppm relative to the mass of the diammonium phosphate raw material.
[0157] The mixed slurry is ground to obtain a mixture; the mixture is spray-dried and granulated to obtain a precursor; the precursor is pre-fired in oxygen to obtain a pre-fired product; the pre-fired product is sintered under a protective atmosphere of nitrogen, the constant temperature sintering temperature is 780° C., the sintering time is 8 hours, and a sintered product is obtained;
[0158] The sintered product is crushed to obtain single crystal or quasi-single crystal granular lithium iron phosphate material.
[0159] The secondary particles are mixed with the single crystal or quasi-single crystal particles in proportion to prepare the positive electrode active material.
[0160] 2) Preparation of positive electrode
[0161] The above positive electrode active material accounting for 97wt% of the solid mass in the positive electrode slurry, 1wt% of the conductive agent conductive carbon black, and 2wt% of the binder polyvinylidene fluoride are mixed, and then N-methylpyrrolidone is added and stirred to disperse into a positive electrode slurry. Then the positive electrode slurry is coated on aluminum foil. After the above is completed, it is dried, cold pressed, cut, and prepared to obtain a positive electrode sheet.
[0162] 3) Preparation of negative electrode sheet
[0163] 95 wt% of artificial graphite as a negative electrode active material, 1.0 wt% of conductive carbon black as a conductive agent, 2.0 wt% of a binder such as styrene-butadiene rubber (SBR) and 2.0 wt% of a thickener such as sodium carboxymethyl cellulose (CMC-Na) were mixed, deionized water was added, stirred, and dispersed to prepare a negative electrode slurry.
[0164] Then the negative electrode slurry is coated on the Cu foil. After both sides are completed, it is dried, cold pressed, cut and sliced to prepare the negative electrode sheet.
[0165] 4) Preparation of electrolyte
[0166] In an argon atmosphere glove box (H 2 O<0.1ppm, O 2 <0.1ppm), mix the organic solvent ethylene carbonate (EC) / ethyl methyl carbonate (EMC) in a volume ratio of 3 / 7, add 12.5% LiPF 6 Lithium salt (LiPF 6 The mass percentage of lithium salt in the electrolyte is 12.5%) is dissolved in an organic solvent and stirred evenly to obtain an electrolyte.
[0167] 5) Preparation of isolation membrane
[0168] A polyethylene film (PE membrane) is used as the isolation membrane.
[0169] 6) Battery preparation
[0170] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound and hot-pressed to obtain a bare cell. The bare cell is placed in an outer package, injected with the prepared electrolyte, and packaged, injected, formed, vented, and other processes to obtain a lithium-ion battery.
[0171] In Examples 2-13, the content of impurity elements was adjusted. The content of M1 and Ma elements in the positive electrode active material was adjusted by adjusting the impurity content of transition metal oxides in the iron source; the content of M2 and Mb elements in the positive electrode active material was adjusted by adjusting the impurity content of alkali metal and alkaline earth metal oxides in the lithium source and phosphorus source.
[0172] In Examples 14-19, the particle sizes of the secondary particles and the primary particles were adjusted by:
[0173] The particle size of the secondary particles can be controlled by adjusting the spray system parameters during spray drying, such as spray pressure, spray flow rate, and solid content of the spray slurry. The particle size of the primary particles can be adjusted by adjusting the sintering temperature and sintering time.
[0174] In Examples 20-22, the mass ratio of secondary particles to single crystal or quasi-single crystal particles was adjusted, and the specific parameters are shown in the table.
[0175] The preparation method of Example 23 is substantially the same as that of Example 1, except that the isolation membrane is a modified isolation membrane. The preparation method of the isolation membrane comprises:
[0176] The silica particles were mixed with anhydrous toluene and γ-aminopropyltriethoxysilane by ultrasonication until there was no agglomeration, and then refluxed and cleaned to remove the excess silanization agent to obtain surface amino-functionalized silica microspheres.
[0177] The surface amino-functionalized silica microspheres and PVDF binder were mixed in an organic solvent (NMP) at a mass ratio of 20:80 for 2 hours, and the viscosity was adjusted to a range of 100 to 500 mPa·s to prepare a coating slurry;
[0178] The coating slurry is coated on two surfaces of the porous substrate PE respectively by spraying, and the modified isolation membrane is obtained after washing and drying.
[0179] The preparation methods in Comparative Examples 1 and 3 are substantially the same as those in Example 1, except that Comparative Examples 1 and 3 only include secondary particles, and do not include single crystal or single crystal-like particles.
[0180] The preparation methods in Comparative Examples 2 and 4 are substantially the same as those in Example 1, except that the contents of M1 and Ma elements in the positive electrode active material are adjusted in Comparative Examples 2 and 4 by adjusting the content of transition metal oxide impurities in the iron source.
[0181] 2. Performance Test
[0182] 1. Average particle size test of secondary particles and single crystal or quasi-single crystal particles
[0183] The cross-section of the positive electrode piece was observed by scanning electron microscopy. The scanning electron microscope was used for observation. The particle size area analysis was performed on the obtained scanning electron microscope image of the electrode cross-section using Avizo 3D software. The particle size of the positive electrode active material was fitted and calculated. The total value of the statistical secondary particle size was divided by the total number of secondary particles as the average particle size of the secondary particles; the total value of the statistical single crystal or quasi-single crystal particle size was divided by the total number of single crystal or quasi-single crystal particles as the average particle size of the single crystal or quasi-single crystal particles.
[0184] 2. Particle size test of primary particles
[0185] The cross-section of the secondary particles was observed using a scanning electron microscope to observe their particle morphology and measure the particle size of the primary particles inside the secondary particles. The long diameter of the primary particles was taken as the particle size of the primary particles, and the total value of the particle size of the primary particles divided by the total number of primary particles was taken as the average particle size of the primary particles.
[0186] 3. Measurement of elements and their contents in secondary particles and single crystal or quasi-single crystal particles
[0187] The element content is tested with reference to the chemical analysis method for nano-lithium iron phosphate in the national standard GB T33822-2017.
[0188] 4. Gram capacity test method
[0189] The gram capacity of 1 / 3C at 25°C is used to characterize the capacity of the battery. The specific detection process is briefly described as follows: place the battery in a 25°C oven environment and let it stand for 2 hours until the battery temperature remains at 25°C; use 1 / 3C DC charging to a voltage of 2.0V; pause for 5 minutes; use l / 3C constant current charging to a voltage of 3.65V, and constant voltage charging to a current less than or equal to 0.05C; pause for 5 minutes; l / 3C constant voltage discharge to a voltage of 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity can be calculated.
[0190] 5. Low temperature performance test method
[0191] The lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, then charged to 3.65V at a constant current rate of 0.33C, and then charged to 0.05C at a constant voltage rate of 3.65V. After the charging was completed, the tested batteries were left to stand at 25°C for 2 hours, and then discharged to 2.5V at a DC rate of 0.5C, and the discharge capacity at room temperature was recorded as C0;
[0192] The lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, then charged to 3.65V at a constant current rate of 0.33C, and then charged to 0.05C at a constant voltage rate of 3.65V. After charging, the tested batteries were left at -20°C for 2 hours, and then discharged to 2.5V at a DC rate of 0.5C, and the -20°C discharge capacity was recorded as C1. The capacity retention rate of the lithium ion battery at -20°C is: (C1 / C0)×100%.
[0193] 6. Cyclic performance test method
[0194] Adopt 1C / 1C cycle at 60℃ to detect the number of cycles when the battery capacity decays to 80% of the initial value. The specific process is briefly described as follows: place the battery in a 25℃ oven and let it stand for 2h until the battery temperature remains at 25℃; charge at 1C constant current to 3.65V; continue constant voltage charging until the charging current is less than 0.05C; let it stand for 5min; discharge at 1C constant current to 2.5V; pause for 5min. This is a charge and discharge cycle. Repeat the above steps continuously to measure the number of cycles when the battery capacity decays to 80% of the initial value.
[0195] 7. Self-discharge K value test method
[0196] Place the battery in a 25°C oven, let it stand for 30 minutes, charge to 3.65V with a constant current of 1 / 3C, continue constant voltage charging until the charging current is less than 0.05C and then cut off; let it stand for 30 minutes; discharge to 2.0V with a constant current of 1C; let it stand for 30 minutes; discharge to 2.0V with a constant current of 0.1C; let it stand for 30 minutes; charge to 21% SOC with a constant current of 0.1C; let it stand for 30 minutes; let it stand for 12 hours; test voltage, recorded as OCV1, in mV, let it stand for 24 hours; test voltage, recorded as OCV2, in mV; K value = (OCV1-OCV2) / 24h, in mV / h.
[0197] III. Analysis of test results of various embodiments and comparative examples
[0198] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1 to 3 below.
[0199] Table 1
[0200]
[0201] Table 2
[0202]
[0203] Table 3
[0204]
[0205] From the comparison between the embodiment and the comparative example, it can be seen that the positive electrode active material in the embodiment of the present application includes secondary particles and single crystal or quasi-single crystal particles, the secondary particles are aggregated by primary particles and the secondary particles also contain M1 elements, the M1 elements include Ni, Cr, Cu, Zn, Co, Mn elements, based on the total mass of the secondary particles, the mass content X1 of the M1 element is 500ppm-5000ppm, and can be optionally 800ppm-2000ppm; the single crystal or quasi-single crystal particles contain Ma elements, the Ma elements include transition metal elements other than iron, based on the total mass of the single crystal or quasi-single crystal particles, the mass content of the Ma element is X2, and X2 is less than X1. The positive electrode active material can take into account the electrochemical performance of the secondary battery at low cost.
[0206] From the comparison of the embodiment and the comparative example in Table 1, it can be seen that the single crystal particles contain Ma (Ni, Cr, Cu, Zn, Co, Mn) elements. Based on the total mass of the single crystal particles, when the mass content X2 of the Ma element is 20ppm-450ppm, the secondary battery has a lower self-discharge level.
[0207] It can be seen from Examples 5-7 that the single crystal particles contain Ma (Ni, Cr, Cu, Zn, Co, Mn, V) elements. When the mass content X2 of the Ma element is 100ppm-300ppm based on the total mass of the single crystal particles, the secondary battery has both low cost and low self-discharge level.
[0208] The secondary particles further contain M2 (Na, K, Ca, Al, Mg) elements. When the mass content of the M2 elements is 650 ppm-8000 ppm based on the total mass of the secondary particles, the cost of the secondary battery is further reduced.
[0209] It can be seen from Examples 11-13 that the single crystal or quasi-single crystal particles contain Mb (Na, K, Ca, Al, Mg) elements. When the mass content of the Mb element is 20ppm-550ppm based on the total mass of the single crystal particles, the secondary battery has a higher capacity level.
[0210] It can be seen from Examples 1 and 11-13 that the single crystal particles contain Mb (Na, K, Ca, Al, Mg) elements. When the mass content of the Mb element is 100ppm-300ppm based on the total mass of the single crystal particles, the secondary battery has both low cost and high capacity level.
[0211] From the comparison between the embodiment and the comparative example, it can be seen that the average particle size of the secondary particles is r, the average particle size of the single crystal particles is R2, and when 2≤r / R2≤30, the secondary battery has high cycle stability and compaction density.
[0212] It can be seen from Examples 14-16 and Example 1 that the average particle size of the secondary particles is r, the average particle size of the single crystal particles is R2, and when 4≤r / R2≤10, the cycle stability and compaction density of the secondary battery are further improved.
[0213] From the comparison between the embodiment and the comparative example, it can be seen that the average particle size of the primary particles is R1, the average particle size of the single crystal particles is R2, and when 2≤R2 / R1≤20, the secondary battery has excellent low temperature performance.
[0214] It can be seen from Examples 17-19 and Example 1 that the average particle size of the primary particles is R1, the average particle size of the single crystal particles is R2, and when 6≤R2 / R1≤10, the secondary battery has both excellent low temperature performance and cycle stability.
[0215] It can be seen from the comparison between the examples and the comparative examples that when the mass ratio of the secondary particles to the single crystal particles is 1:9-4:6, the battery has both low cost and high performance.
[0216] It can be seen from Examples 20-22 and Example 1 that when the mass ratio of secondary particles to single crystal particles is 2:8-3:7, the cost and performance of the battery are further balanced.
[0217] It can be seen from Example 23 and Example 1 that when the modified isolation membrane is used in the secondary battery, the cycle stability of the battery is further improved and the battery self-discharge K value is further reduced.
[0218] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises: (i) secondary particles, wherein the secondary particles are mainly aggregated from primary particles and further contain M1 elements, wherein the M1 elements contain transition metal elements other than iron, and the mass content of the M1 elements is X1, 500ppm≤X1≤5000ppm, and optionally 800ppm≤X1≤2000ppm based on the total mass of the secondary particles; and (ii) Single crystal or quasi-single crystal particles, wherein the single crystal or quasi-single crystal particles contain Ma elements, wherein the Ma elements contain transition metal elements other than iron, and the mass content of the Ma elements is X2 based on the total mass of the single crystal or quasi-single crystal particles, and X2 is less than X1.
2. The positive electrode active material according to claim 1, characterized in that The single crystal or quasi-single crystal particles contain Ma elements, and the Ma elements contain transition metal elements other than iron. Based on the total mass of the single crystal or quasi-single crystal particles, the mass content X2 of the Ma element is 20ppm-450ppm, and can be optionally 100ppm-300ppm.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The secondary particles also contain M2 elements, and the M2 elements contain at least one of alkali metal elements, alkaline earth metal elements, and boron elements except lithium. Based on the total mass of the secondary particles, the mass content of the M2 elements is 650ppm-8000ppm, and can be optionally 1000ppm-5000ppm.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The single crystal or quasi-single crystal particle further contains Mb element, and the Mb element contains at least one of alkali metal elements, alkaline earth metal elements, and boron group elements except lithium element. Based on the total mass of the single crystal or quasi-single crystal particle, the mass content of the Mb element is 20ppm-550ppm, and can be optionally 100ppm-300ppm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The average particle size of the secondary particles is r, and the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤r / R2≤30, and can be optionally 4≤r / R2≤10.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The average particle size of the primary particles is R1, and the average particle size of the single crystal or quasi-single crystal particles is R2, 2≤R2 / R1≤20, and can be optionally 6≤R2 / R1≤10.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The average particle size r of the secondary particles is 1.2um-18um, and can be optionally 2.4um-6um.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that The average particle size R1 of the primary particles is 30nm-300nm, and can be 60nm-100nm.
9. The positive electrode active material according to any one of claims 1 to 8, characterized in that The mass ratio of the secondary particles to the single crystal or quasi-single crystal particles is 1:9-4:6, and can be optionally 2:8-3:
7.
10. The positive electrode active material according to any one of claims 1 to 9, characterized in that M2 and Mb each independently include at least one of Na, K, Ca, Al, and Mg, and M1 and Ma each independently include at least one of Ni, Cu, Zn, Mn, Cr, and Co.
11. The positive electrode active material according to any one of claims 1 to 10, characterized in that The positive electrode active material includes lithium-containing phosphate. Optionally, the positive electrode active material includes lithium iron phosphate and a coating modification material thereof.
12. A positive electrode sheet, characterized in that: The invention comprises a positive electrode film layer, wherein the positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 11.
13. A secondary battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 11 or the positive electrode sheet according to claim 12.
14. The secondary battery according to claim 13, characterized in that: The secondary battery further includes a separator, and the separator includes at least one of hydroxyl, amino, carboxyl, and ester functional groups.
15. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 13 or 14.
Citation Information
Patent Citations
Cathode materials, cathodes, and lithium secondary batteries containing spinel-structured lithium manganese-based cathode active materials
CN110582875A
Positive electrode material and lithium ion battery containing same
CN111682185A
Positive pole piece for secondary battery, secondary battery, battery module, battery pack and device
CN114556614A
Positive electrode material, positive electrode plate, lithium secondary battery, battery module, battery pack and device
CN116097468A
Positive active material, method of preparing the same, and lithium battery including the positive active material
US20140106222A1
Cited By
Positive electrode active material, positive electrode sheet, secondary battery and electric device
EP4654292A1